PECULIARITIES OF SOCIAL AND HUMANITARIAN TRAINING OF FUTURE NAVIGATORS AS A FACTOR OF FORMATION THEIR SOCIOCULTURAL COMPETENCE (Education in the 21st Century, 2023)
The paper deals with the problem of formation the future navigators’ sociocultural competence. It is stated that the processes of development of Ukraine as an independent sovereign state, the establishment of relations between peoples actualize the issue of forming the sociocultural personality of future navigators of international voyages. The author highlights that recent development trends and requirements of the maritime labor market lead to a revision of the training system for future navigators taking into account the formation of their sociocultural competence. It is determined that the sociocultural competence of future navigators of international voyages is formed mainly on the basis of their study of the national culture of different countries of the world at English classes. This allows students to realize the difference between their native culture and other cultures, as well as to acquire the ability to overcome sociocultural differences. In the article it is emphasized that saturation of cadets' social and humanitarian training with sociocultural content occurs not only when they study “English language of a professional orientation”, but also when they master such academic disciplines as: “Philosophy”, “History and Culture of Ukraine”, “Psychology”, “Marine Resources Management "," Geography of shipping and ocean routes of the world ". The author focuses on sociocultural knowledge as the foundation of intercultural communication and states that an important direction in the process of social and humanitarian training is the formation of the future navigator as a cultural mediator in situations of intercultural communication, as a subject of dialogue of cultures. The author has formulated the features of an effective process of social and humanitarian training of future navigators, they are: expansion of the sociocultural component in the process of teaching social and humanitarian disciplines to the extent that is considered sufficient to enhance self-organization of cadets' knowledge in unusual conditions or in the course of solving problem situations; the formation of cadets' motivation to master sociocultural knowledge; orientation of the socio-humanitarian training of future navigators towards resolving the contradictions between personal and public interests; development of cadets' searching skills to expand socio-cultural training; creating conditions for cadets to learn the traditional (knowledge, skills) and non-traditional (creative activities experience) components of the content of social and humanitarian disciplines.